Lessons from the development of the Guiding Principles on Internal Displacement - Roberta Cohen (Forced Migration Review, 2014)
The Guiding Principles on Internal Displacement filled a major gap in the international protection system for uprooted people. Whether their development holds lessons for those seeking to develop standards in the migration field remains a question to explore.